2011
DOI: 10.1007/s10841-011-9435-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design of butterfly occupancy surveys and testing if occupancy converts to abundance for sparse populations

Abstract: Occupancy has several important advantages over abundance methods and may be the best choice for monitoring sparse populations. Here we use simulations to evaluate competing designs (number of sites vs. number of surveys) for occupancy monitoring, with emphasis on sparse populations of the endangered Karner blue butterfly (Lycaeides melissa samuelis Nabokov). Because conservation planning is usually abundance-based, we also ask whether detection/non-detection data may reliably convert to abundance, hypothesizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 66 publications
(71 reference statements)
0
21
0
Order By: Relevance
“…Therefore, higher levels of survey effort are often recommended for rare species (e.g. Bried and Pellet 2012). In summary, we demonstrated a useful sampling protocol for assessing broad diversity patterns of relatively abundant species in response to environmental gradients (Vellend et al 2008).…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, higher levels of survey effort are often recommended for rare species (e.g. Bried and Pellet 2012). In summary, we demonstrated a useful sampling protocol for assessing broad diversity patterns of relatively abundant species in response to environmental gradients (Vellend et al 2008).…”
Section: Discussionmentioning
confidence: 80%
“…While patch area and previous occupancy as surrogates for population size can suffice for predicting average occupancy -and thus average abundance -predictions of yearly changes in occupancy ignorant of population sizes would be biased towards the average case. But trying to predict extinction dynamics of individual populations and estimate actual, not average, abundances using the same models could lead to biased estimates and higher uncertainty (Harrison et al 2011, Bried andPellet 2012). Generally, this calls for caution when using occupancy as a surrogate for abundance in some contexts.…”
Section: Effect Of Abundance On Occupancymentioning
confidence: 99%
“…Bried and Pellet 2012;LaCommare et al 2012;Williams and Thomas 2009). In many cases, the relationship between them is unknown and consequently a linear relationship must be assumed (LaCommare et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Bried and Pellet (2012) concluded that the minimum allowable effort for occupancy monitoring of the Karner blue butterfly was 360 (40 sites x 9 surveys) for the spring generation and 200 (20 sites x 10 surveys) for the summer generation. Keizer-Vlek et al (2012) found that more than 1000 sites must be sampled to detect a 40% change in the frequency for monitoring rare river inhabiting macroinvertebrates (50 sites for common species).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation